Dual challenge inside the womb: a case report of concomitant fetal atrio-ventricular block associated with maternal anti-SSA antibodies and fetal tachyarrhythmia diagnosed as Wolff-Parkinson-White syndrome after birth - Chícharo, Ana Teodósio; Rebelo, Mónica; Lopes, Ana Rita; Saavedra, Maria João; Paramés, Maria Filipa; Araújo, Ana Rita; Cruz-Machado, Ana Rita; Pinto, Luísa; Capela, Susana (Frontiers in Immunology, 2024)
Fetal autoimmune atrioventricular block (AVB) is a rare but potentially life-threatening condition. It results from the passage of maternal anti-SSA/Ro or Anti SSB/La auto-antibodies into the fetal circulation, leading to inflammation and fibrosis of the AV node and often to irreversible damage. Besides AVB, these antibodies can also cause cardiomyopathies, but there is no evidence linking them to tachyarrhythmias. We present the case of a patient with significant risk factors for fetal AVB: a prior history of hydrops fetalis, high anti-SSA/Ro antibody levels and hypothyroidism. In this case, the use of dexamethasone and intravenous immunoglobulin may have contributed to reversing the first-degree atrioventricular block detected at 19 weeks of gestation. Additionally, at 21 weeks, the fetus developed a tachyarrhythmia that needed treatment with flecainide. Soon after the birth, the newborn underwent ECG Holter and Wolff-Parkinson-White Syndrome (WPWS)was diagnosed. To our knowledge, the coexistence of fetal AVB and WPWS has never been described.